The Correlation Between Reading Comprehension and Writing Ability in Descriptive Text - Juriati, Dewi Eka; Ariyanti, Ariyanti; Fitriana, Rinda (Southeast Asian Journal of Islamic Education, 2018)
This study focuses on correlation between reading comprehension and writing ability in descriptive text. The researchers collect the data through two instruments, i.e. test of reading comprehension and descriptive text writing. This research is researched quantitatively and SPSS was used to analyse the data.  Then, the result of the study shows that mean score of reading comprehension is 72.47. It means that the students reading comprehension was good. Meanwhile, the mean score of writing ability in descriptive text is 61.14. In addition, the researchers found that r-counted is 0.098, and the r-table with n = 108 (df-2 = 106) with significance level = 95% (α = 0.05) is 0.189. It indicates low correlation between the two variables.